Lung volume reduction coil treatment for patients with severe emphysema: a European multicentre trial. Issue 11 (2nd June 2014) - Deslee, Gaëtan; Klooster, Karin; Hetzel, Martin; Stanzel, Franz; Kessler, Romain; Marquette, Charles-Hugo; Witt, Christian; Blaas, Stefan; Gesierich, Wolfgang; Herth, Felix J F; Hetzel, Juergen; van Rikxoort, Eva M; et al.
Abstract : Background: The lung volume reduction (LVR) coil is a minimally invasive bronchoscopic nitinol device designed to reduce hyperinflation and improve elastic recoil in severe emphysema. We investigated the feasibility, safety and efficacy of LVR coil treatment in a prospective multicentre cohort trial in patients with severe emphysema. Methods: Patients were treated in 11 centres. Safety was evaluated by recording all adverse events, efficacy by the St George's Respiratory Questionnaire (SGRQ) as primary endpoint, and pulmonary function testing, modified Medical Research Council dyspnoea score (mMRC) and 6-min walk distance (6MWD) up to 12 months after the final treatment. Results: Sixty patients (60.9 ± 7.5 years, forced expiratory volume in 1 s (FEV1 ) 30.2 ± 6.3% pred) were bronchoscopically treated with coils (55 bilateral, 5 unilateral), with a median of 10 (range 5–15) coils per lobe. Within 30 days post-treatment, seven chronic obstructive pulmonary disease exacerbations (6.1%), six pneumonias (5.2%), four pneumothoraces (3.5%) and one haemoptysis (0.9%) occurred as serious adverse events. At 6 and 12 months, respectively, ΔSGRQ was −12.1±12.9 and −11.1±13.3 points, Δ6MWD was +29.7±74.1 m and +51.4±76 m, ΔFEV1 was +0.11±0.20 L and +0.11±0.30 L, and ΔRV (residual volume) was −0.65±0.90 L and −0.71±0.81 L (all p<0.01). Post hoc analyses showed significant responses for SGRQ, 6MWD and RV in patients with both heterogeneous and homogeneous emphysema. Conclusions: LVR coil treatment results in significant clinical improvements in patients with severe emphysema, with a good safety profile and sustained results for up to 1 year. Trial registration number: NCT01328899.